EFFECTIVENESS OF SCYLLA SERRATA CHITOSAN FOR INCISION WOUND HEALING IN ORAL MUCOSA OF RATTUS NORVEGICUS - RUSDY, HENDRY; AGUSNAR, HARRY; HANAFIAH, OLIVIA AVRIYANTI; SIREGAR, INDRA BASAR; SYADANA, NASYWA TIARA (International Journal of Applied Pharmaceutics, 2025)
Objective: To evaluate the effectiveness of Scylla serrata–derived chitosan gel in promoting healing of oral mucosal incision wounds in Rattus norvegicus. Methods: Twenty-five male Rattus norvegicus were randomly divided into five groups: a positive control group (Gengigel), a negative control group (CMC-Na gel), and three treatment groups receiving 1%, 3%, or 5% chitosan gel. Chitosan concentrations were selected based on prior evidence of therapeutic potential. Incisions were made on the buccal mucosa, and erythema and wound length were assessed on days 1, 3, and 7 post-incision. Erythema data were analyzed using the Pearson chi-square test, while wound length data were evaluated using the Kruskal–Wallis test. Results: All chitosan gel groups (1%, 3%, and 5%) demonstrated significantly greater reductions in erythema and wound length compared with the negative control group (p < 0.05). Among the treatment concentrations, 3% chitosan gel produced the most effective wound-healing response. Conclusion: Scylla serrata chitosan gel effectively reduces erythema and accelerates wound closure in oral mucosal incision wounds of Rattus norvegicus, with 3% identified as the optimal concentration for promoting healing.